Akhlak Nabi Muhammad SAW dalam Berdakwah: Kajian Pada Surah Ali-‘Imran Ayat 159 - Nawa Nuril Husna; Syamsul Arifin (Al-Kindi, 2025)
This article aims to analyze the morals and methods of preaching of the Prophet Muhammad saw in preaching based on Surah Ali-‘Imran verse 159. This study uses a qualitative approach with a library research method. Primary data is taken from the Qur'an Surah Ali-‘Imran verse 159, while secondary data includes books, articles and scientific works related to the preaching and morals of the Prophet Muhammad saw. The analysis of this study shows that the morals of the Prophet Muhammad saw in preaching are reflected through a gentle attitude, forgiving, asking for forgiveness or praying for the goodness of others, always deliberating, and trusting in Allah Swt. These morals are the foundation for the effectiveness of inclusive and humanistic preaching. Surah Ali-‘Imran verse 159 emphasizes that gentleness and exemplary morals are the keys to the success of the Prophet Muhammad's preaching.